AUTHENTIC ASSESSMENT IN LITERAL AND INFERENTIAL READING COMPREHENSION FOR UNIVERSITY STUDENTS - Heriyawati, Dwi Fita (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2013)
The teaching of English as a foreign language in Indonesia is widely developed time to time. In the teaching of English, reading comprehension has an important role, because through reading the text the students will acquire the knowledge of science and technology. Furthermore, the teachers have also have to measure the studentsâ performance in comprehending the reading text. The use of authentic assessment in the literal and inferential reading comprehension can help the students and also the teachers in comprehending what they learn in the text. The authentic assessment will reduce the tension of the students while they do reading test. Teachers also can implement the teaching learning process and the assessment efficiently. This paper aim to give some contribution to the readers how to select a good reading assessment that should be given for the university students. Hopefully, this paper can give a contribution to the teachers in Indonesia to be wise in selecting a good reading text and reading assessment in order to get the purpose of reading itself.Keywords: authentic assessment, reading comprehension, literal and inferential comprehension